2017
DOI: 10.1002/rmb2.12072
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective cohort study of the risk factors for secondary infertility following hysteroscopic metroplasty of the uterine septum in women with recurrent pregnancy loss

Abstract: PurposeA hysteroscopic metroplasty was performed for women with recurrent pregnancy loss owing to a uterine septum, following which some women became infertile. The aim of this study was to elucidate the risk factors of secondary infertility 1 year after hysteroscopic metroplasty for a uterine septum.MethodsA retrospective, single‐center, cohort study included women with a history of at least two miscarriages that had been attributed to a uterine septum who underwent a hysteroscopic metroplasty. The patients’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…However, at present, there is no evidence to support the use of this surgical procedure in these women, and randomized controlled trials are urgently needed. [14] Several studies [7,11,15,16] reported an increase in pregnancy rate after metroplasty in groups of infertile patients, ranging from 23% to 80.6%. Unfortunately, low numbers of patient, heterogeneity, and retrospective design, as well as the absence of a control group make the results of these studies hard to interpret.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, at present, there is no evidence to support the use of this surgical procedure in these women, and randomized controlled trials are urgently needed. [14] Several studies [7,11,15,16] reported an increase in pregnancy rate after metroplasty in groups of infertile patients, ranging from 23% to 80.6%. Unfortunately, low numbers of patient, heterogeneity, and retrospective design, as well as the absence of a control group make the results of these studies hard to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Ono et al [7] published a retrospective, single-center, cohort study including 31 patients with a history of at least 2 miscarriages due to a uterine septum who underwent a hysteroscopic resection. In this study, the postoperative pregnancy rate was 83.9%, and at 1 year postoperatively, 5 women remained persistent infertile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that RPL occurs in 1%-3% of couples who try to conceive (3). The prevalence of anatomical uterine anomalies in women experiencing RPL varies from 15% to 42% according to different studies (6)(7)(8)(9)(10). Congenital uterine anomalies are associated with 7%-28% of RPL (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…These mainly include septate uteri and more rarely arcuate or bicorporeal uteri. Acquired uterine anomalies are associated with 6%-15% of RPL (6)(7)(8)(9)(10). These include submucosal myomas, intrauterine adhesions (IUAs), and endometrial polyps.…”
mentioning
confidence: 99%